Standing in the breach : the significance and function of the saints in the letters of Barsanuphius and John of Gaza - Torrance, A (Johns Hopkins University Press, 2009)
In this article I attempt to approach the concept of the saint in late antiquity from a theological rather than a socio-historical perspective. Using the abundant correspondence of Barsanuphius and John of Gaza, I look at how they conceived of the saints, the unmistakable importance they attached to their prayers and intercessions, and how the saints fit into Barsanuphius and John’s broader Christian framework. I emphasize that the importance of the ἅγιοι is not constrained to their locality, and that their role for the two Gazan ascetics is not at all bound up with projects of self-promotion.